2010
DOI: 10.2981/09-028
|View full text |Cite
|
Sign up to set email alerts
|

Concealment from predators drives foraging habitat selection in brood‐rearing Alpine black grouse Tetrao tetrix hens: habitat management implications

Abstract: Declines of Alpine black grouse Tetrao tetrix populations have been linked to increasing disturbance by recreation and degradation of breeding habitat due to changes in land-use, especially abandonment of traditional farming practices. Appropriate forest, shrubland and grassland management may mitigate the negative effects of land abandonment. The habitat associations and trophic requirements of brood-rearing Alpine black grouse hens were appraised to inform effective habitat management policies. We measured t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…Signorell et al (2010) observed higher amounts of epigeal and epiphytic arthropod biomass in open grassland habitats compared to shrublands with scattered trees. However, they observed black grouse brood-rearing hens trading-off food biomass for habitat cover, with the hens apparently selecting shrublands with scattered coniferous trees to reduce predation risk (Signorell et al 2010).…”
Section: Habitat Use Of Black Grousementioning
confidence: 83%
See 1 more Smart Citation
“…Signorell et al (2010) observed higher amounts of epigeal and epiphytic arthropod biomass in open grassland habitats compared to shrublands with scattered trees. However, they observed black grouse brood-rearing hens trading-off food biomass for habitat cover, with the hens apparently selecting shrublands with scattered coniferous trees to reduce predation risk (Signorell et al 2010).…”
Section: Habitat Use Of Black Grousementioning
confidence: 83%
“…According to Johnston and Holberton (2009), high abundance of ants and other arthropods is associated with an open forest structure, allowing for the development of the rich ericaceous understorey, which is also essential for black grouse (Beeston et al 2005;Starling-Westerberg 2001). Signorell et al (2010) observed higher amounts of epigeal and epiphytic arthropod biomass in open grassland habitats compared to shrublands with scattered trees. However, they observed black grouse brood-rearing hens trading-off food biomass for habitat cover, with the hens apparently selecting shrublands with scattered coniferous trees to reduce predation risk (Signorell et al 2010).…”
Section: Habitat Use Of Black Grousementioning
confidence: 92%
“…alpenrose Rhododendron ferrugineum, bilberry Vaccinium myrtillus, northern bilberry Vaccinium uliginosum, dwarf juniper Juniperus communis nana, heather Calluna vulgaris, bearberry Arctostaphylos uva-ursi and crowberry Empetrum nigrum) and grasses (e.g. matgrass Nardus stricta, Calamagrostis villosa) represent a characteristic fieldlayer in all areas (Signorell et al 2010). The study areas are characterised by a subcontinental to continental climate, with warm, dry summers and cold, relatively wet winters (Reisigl and Keller 1999).…”
Section: Study Areamentioning
confidence: 99%
“…Signorell et al 2010) was described through a simple visual ordinal estimate of structural heterogeneity with three levels (low, middle and high, see Online Resource 1). Predictors of vegetation heterogeneity were estimated for Moreover, average habitat feature height (0-3, ascending), number of stumps and grazing activity (presence-absence) were also considered as structural predictors.…”
Section: Vegetation Structurementioning
confidence: 99%
“…This may also affect the capercaillie in Switzerland, which selects for open and grazed forests during winter (Sachot et al, 2003). Lower biodiversity might be a consequence of reduced grazing pressure as well as negative impacts on the trade-offs between cover and food-searching that brood-rearing hens exhibit (Signorell et al, 2010). By contrast, in Britain, over-grazing by both red deer (Cervus elaphus) and domestic sheep (Ovis aries) is associated with lower densities of black grouse, lower insect abundance and reduce black grouse reproduction (Baines, 1996;Calladine et al, 2002).…”
Section: Intensified Land-usementioning
confidence: 99%